Pengaruh Kepemimpinan dan Disiplin terhadap Motivasi Kerja Serta Dampaknya pada Kinerja Pegawai Bidang Pelayanan Langsung Rumah Sakit Umum Nurdin Hamzah Kabupaten Tanjung Jabung Timur - Husni Thamrin; Saiyid Syeikh; Sudirman Sudirman (Universitas Batanghari Jambi, 2023)
Achievement or job performance is the qualitative and quantitative result of work done when tasks are completed in accordance with assigned responsibilities. Performance is a measure of the success of health services and reflects the responsibilities of service organizations within the framework of good governance. Hospital Performance refers to the realization of the goals set by medical and administrative personnel. The Institute of Management Development (IMD) stated in the World Competitiveness Yearbook 2022 report that Indonesia's competitiveness has now risen from 38th in 2020 to 44th. According to the results of Nurdin Hamzah Hospital's 2022 staff performance review, it is still not the best in terms of average performance. The aim of this study was to analyze the effect of leadership and discipline on job motivation and its impact on employee performance in the direct service area of Nurdin Hamzah General Hospital, East Tanjung Jabung Regency. The sample is drawn in the way of overall sampling, drawn from all direct service personnel, up to 108 people. According to the results of partial significance test (t statistical test), it is found that the leadership part has a significant impact on employee performance, the discipline part has no significant impact on employee performance, and the motivation part has a significant impact on employee performance. Based on the results of simultaneous analysis (F-test), the model in this study was proved to be correct/feasible. From this it can be concluded that leadership and discipline simultaneously affect performance through variable motivation.